2020
DOI: 10.1093/ageing/afaa056
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic statistical model for predicting the risk of death among older Chinese people, using longitudinal repeated measures of the frailty index: a prospective cohort study

Abstract: Background Frailty is a common characteristic of older people with the ageing process. We aimed to develop and validate a dynamic statistical prediction model to calculate the risk of death in people aged ≥65 years, using a longitudinal frailty index (FI). Methods One training dataset and three validation datasets from the Chinese Longitudinal Healthy Longevity Survey (CLHLS) were used in our study. The training dataset and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…In this study, we used multiple, repeated FI measurements from 4 large cohort studies of community-dwelling older adults to predict mortality. Similar to 2 previous studies (8,9), we also found that the current frailty level predicts mortality risk. Different from previous work, we furthermore differentiated between baseline FI differences and FI change over time.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In this study, we used multiple, repeated FI measurements from 4 large cohort studies of community-dwelling older adults to predict mortality. Similar to 2 previous studies (8,9), we also found that the current frailty level predicts mortality risk. Different from previous work, we furthermore differentiated between baseline FI differences and FI change over time.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, we have shown that the FI can be used to monitor frailty changes and how these are related to mortality on the population level. In addition, joint models also provide a potential means to utilize repeated frailty measurements-which are increasingly available based on routinely collected data in clinical practice (10,19)-to predict individual-level health outcomes dynamically (9). We thus suggest to assess dynamic frailty (4,5) repeatedly in patients to evaluate their respective mortality risk and to assist doctors in their prediction of patient's prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the CLHLS, the FI proved to be a stable and reliable measure of frailty [ 23 ]. In this study, we used nine dimensions to calculate the FI, including cognitive function, chronic illness, ability to perform activities of daily living, activities of daily living, bodily function, self-rated health, hearing ability, visual function, psychological status and other (including heart rhythm, interviewer-rated health status, number of serious illnesses suffered in the past two years) [ 24 ]. The FI is the ratio of the defect score to the total score.…”
Section: Methodsmentioning
confidence: 99%
“…Most of these studies, however, rely on static, one-time assessments, although it has been shown that individuals' FI change over time [7][8][9][10]. A few studies [11][12][13][14][15][16][17] have assessed the relationship between frailty changes or trajectories and mortality, generally finding FI increases or steeper trajectories to be associated with a higher mortality risk. However, mixed results have been found with regard to the question whether FI change captures mortality risk better than and independently of the current (most recent) FI observation [13,17].…”
Section: Introductionmentioning
confidence: 99%